Predoctoral Teaching in Intravenous Conscious Sedation: Ten Years at Glasgow Dental School. Issue 1 (1st January 2013) - Robb, Nigel D.; Leitch, Jason; O'Brian, Conor; Walker, Peter
Abstract : Supervised clinical practice in intravenous conscious sedation was introduced into the predoctoral dental curriculum at Glasgow Dental School and Hospital, United Kingdom, with the appointment of two full‐time academic staff members in 2001. This article reviews the student experience gained in the succeeding ten years. All students administered intravenous sedation to patients during the course as well as assisting with intravenous sedation provided by their peers. The experience was variable, mainly as a result of student and patient attendance. Adverse weather and increasing student numbers also affected student experience. This study demonstrated that it is possible to provide supervised clinical sedation practice for students as part of a predoctoral dental curriculum.